Advocacy, communication, and partnerships: Mobilizing for effective, widespread cervical cancer prevention. (July 2017) - Wittet, Scott; Aylward, Jenny; Cowal, Sally; Drope, Jacqui; Franca, Etienne; Goltz, Sarah; Kuo, Taona; Larson, Heidi; Luciani, Silvana; Mugisha, Emmanuel; Schocken, Celina; Torode, Julie
Abstract: Both human papillomavirus (HPV) vaccination and screening/treatment are relatively simple and inexpensive to implement at all resource levels, and cervical cancer screening has been acknowledged as a "best buy" by the WHO. However, coverage with these interventions is low where they are needed most. Failure to launch or expand cervical cancer prevention programs is by and large due to the absence of dedicated funding, along with a lack of recognition of the urgent need to update policies that can hinder access to services. Clear and sustained communication, robust advocacy, and strategic partnerships are needed to inspire national governments and international bodies to action, including identifying and allocating sustainable program resources. There is significant momentum for expanding coverage of HPV vaccination and screening/preventive treatment in low‐resource settings as evidenced by new global partnerships espousing this goal, and the participation of groups that previously had not focused on this critical health issue. Abstract : Advocacy and communications interventions can help overcome current low levels of access to cervical prevention services in low‐resource settings, especially when implemented through strong partnerships speaking with a common voice.